2007
DOI: 10.1136/adc.2007.120691
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal pro-B-type natriuretic peptide: a measure of significant patent ductus arteriosus

Abstract: Background: B-type natriuretic peptide (BNP) is a marker for ventricular dysfunction secreted as a preprohormone, pro-B-type natriuretic peptide (proBNP), and cleaved into BNP and a biologically inactive fragment, Nterminal pro-B-type natriuretic peptide (NT-proBNP). Little is known about the clinical usefulness of NT-proBNP in preterm infants. Objective: To evaluate the usefulness of plasma NTproBNP in diagnosing haemodynamically significant patent ductus arteriosus (hsPDA) in neonates and examine some factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 32 publications
4
58
0
2
Order By: Relevance
“…These results were similar to those of the recent study using NT-proBNP on day 3 as a marker for HsPDA in preterm infants. 36 Interestingly, infants in the HsPDA group exhibited only a few clinical signs of PDA, most of which were nonspecific (Table 2). Therefore, the NT-proBNP level on day 2-3 may be used as a screening tool in preterm infants for predicting HsPDA and guiding physicians to consider early echocardiographic evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results were similar to those of the recent study using NT-proBNP on day 3 as a marker for HsPDA in preterm infants. 36 Interestingly, infants in the HsPDA group exhibited only a few clinical signs of PDA, most of which were nonspecific (Table 2). Therefore, the NT-proBNP level on day 2-3 may be used as a screening tool in preterm infants for predicting HsPDA and guiding physicians to consider early echocardiographic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…FarombiOghuvbu et al 36 studied serial plasma NT-proBNP levels on day 1, 3, 5 and 10 of life among 49 infants <34 weeks of gestation and found that the plasma NT-proBNP levels on day 3 and day 5, not on day 1 or day 10, were significantly higher in infants with HsPDA. These findings as well as ours suggest that the best timing to measure NT-proBNP level for predicting HsPDA should be at day 2-3 of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oghuvbu et al (2) reported in their study that PDA diameter should be 1,6 mm and above for a diagnosis of hemodynamic PDA and as PDA diameter increased, BNP level increased. ElKhuffash et al (5) reported that BNP level was affected by PDA diameter and LA/Ao ratio after the 12 th hour after birth and with the increase in both of these values BNP increased significantly in the review they published about BNP in preterm babies.…”
Section: Discussionmentioning
confidence: 99%
“…However, supplementary investigations can be beneficial, if clinical findings suggest PDA in centers where ECHO is unavailable. Natriuretic peptide is one of these (2,3). In recent years, use of natriuretic peptide (BNP) as a supplementary investigation in the diagnosis has increased, though not used solely in the diagnosis of PDA.…”
Section: Introductionmentioning
confidence: 99%